Upaya Penegakan Hukum oleh Kepolisian terhadap Pelanggaran Privasi di Media Sosial Facebook di Kota Kupang - Deksin Radja Wila; Debby F.Ng. Fallo; Adrianus Djara Dima (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Facebook is a social activity platform that can be done in cyberspace (unreal), allowing for reciprocal interaction between users, one of which is conducting online buying and selling transactions. Privacy violations on social media can occur in various forms such as the spread of personal information without permission, identity theft, online fraud and many more. These cases not only harm individuals but can also have an impact on the reputation and public trust in social media platforms. This study is an empirical legal research study with a qualitative approach. Data collection techniques were obtained from interviews and documentary studies. The research analysis used descriptive qualitative analysis. The results of the study showed that repressive efforts are law enforcement efforts carried out by the NTT Regional Police in dealing with cases of consumer privacy violations carried out by fake accounts on Facebook social media. The obstacles experienced by the NTT Regional Police in dealing with cases of consumer privacy violations carried out by fake accounts on Facebook social media include: Legal aspects, Law enforcement aspects, Facilities and Facilities aspects, Community aspects, and Cultural aspects.